Microbiological water quality monitoring of four ponds from Lagoa do Sino Farm located in São Paulo State, Brazil (Acta Scientiarum. Biological Sciences, 2021)
This study aimed to evaluate the microbiological quality of the water of four ponds used for irrigation on the Lagoa do Sino Farm, as well as to perform the genotypic characterization of virulence factors in Escherichia coli isolates. Sampling was conducted for 11 months, between 2015 and 2016. Samples were analyzed for the presence of thermotolerant coliforms, E. coli and heterotrophs. DNA was extracted from E. coli isolates, followed by genotypic characterization by polymerase chain reaction. Agricultural activities and pesticides used in the sampling period were documented in order to assess possible relationships between agricultural activities and microbiological water quality. The absence of suitable riparian vegetation around all the ponds was observed, benefiting the entry of organic matter and contaminants in the water body. A high index of thermotolerant coliforms in some months indicated the possibility of the transmission of pathogenic microorganisms in these ponds. The values found in some months were above the regulatory limits for water potability and water intended for irrigation. The agrochemicals used in the period seem to influence the results obtained. All 17 E. coli isolates showed at least one of the virulence genes estA, stx1, stx2, and aatA, indicating enterotoxigenic, enterohaemorrhagic or enteroaggregative nature. The presence of E. coli in the waters may be associated with the presence of animals. The water samples analyzed are not suitable for irrigation of vegetables that are consumed raw and/or low lying fruits ingested without skin removal. It is essential to broaden the control of the use of chemicals, as well as the preservation of riparian vegetation to improve the quality of water used in the farm's agricultural activities.